Mito y realidad: la imagen internacional de México - Anholt, Simon (Revista Mexicana de Política Exterior, 2012)
Simon Anholt invokes the concepts of nation branding and competitive identity in his reflection on how Mexico is perceived by the rest of the world. Mexico, he says, is capable of designing and building itself an image that reflects a rich, pluralistic reality based on tangible evidence, one that offsets the negative press of recent years. In 2010, Mexico was rated 31 out of 50 countries on Anholt-GfK Roper’s Nation Brand Index (nbi). Of all the variables taken into consideration, People, Tourism and Culture were the categories in which Mexico scored best. But although Mexico achieved a middle-of-the range nbi rating, generally speaking, it is a country the world doesn’t know a lot about and the little information it does have has been supplied by America’s culture and information industries. According to Anholt, Mexico needs to focus on winning the right to be perceived as an international leader when it comes to tackling specific global problems like violence, crime and environmental issues.